2018
DOI: 10.1088/1361-6463/aad42c
|View full text |Cite
|
Sign up to set email alerts
|

Spatial-filter-installed Shack–Hartmann sensor for two-dimensional electron density visualization of SF6 arc discharge under strong turbulent flow

Abstract: the detailed diagnosis of the electron density distributions in the current-zero arcs. Hence, this has been an active area of research with early reports in 1980s for SF 6 gas arcs [10][11][12]. However, the electron density determination has been often conducted at only one position in the arcs and decaying arc phenomena have not been intensively examined based on the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 35 publications
1
8
0
Order By: Relevance
“…Those multiple vortices interact with each other, deform, merge, and break up, eventually forming a turbulent field composed of multiscale vortices. Such vortices of thermal plasma-induced turbulence were actually captured in the experimental studies for a DC non-transferred arc plasma jet of argon gas by Pfender et al 1) and a DC transferred arc plasma sustained in SF 6 (sulfur hexafluoride) gas by Inada et al 2,3) Plasma spraying and nanoparticle mass-production are typical applications of thermal plasma. Because vortices convey thermal energy and substances, a turbulent field composed of vortices dominates the transport phenomena in the whole flow system.…”
Section: Introductionmentioning
confidence: 89%
“…Those multiple vortices interact with each other, deform, merge, and break up, eventually forming a turbulent field composed of multiscale vortices. Such vortices of thermal plasma-induced turbulence were actually captured in the experimental studies for a DC non-transferred arc plasma jet of argon gas by Pfender et al 1) and a DC transferred arc plasma sustained in SF 6 (sulfur hexafluoride) gas by Inada et al 2,3) Plasma spraying and nanoparticle mass-production are typical applications of thermal plasma. Because vortices convey thermal energy and substances, a turbulent field composed of vortices dominates the transport phenomena in the whole flow system.…”
Section: Introductionmentioning
confidence: 89%
“…Figure shows the cross section of the nozzle space in our arc device, which we have been using for a fundamental study for arc discharges A half area of this cross section was treated as calculation domain, which is a cylindrical axisymmetric two‐dimensional area. The calculation domain size is 170 × 50 mm.…”
Section: Modeling Of the Arc Plasma In A Nozzlementioning
confidence: 99%
“…In addition, successful or failure interruption is determined in very short time of the order of µs. For this reason, it is important to study the arc extinction phenomena in detail with both experimental and numerical simulation approaches . In our previous experimental approach, we established a new system of decaying arc plasmas using a direct‐current power source and an insulated gate bipolar transistor .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors have found that the decay rate of the electron density in the SF 6 gas arc experimentally obtained are faster than those in the electromagnetic thermofluid simulation under the laminar flow assumption [5] [6],. This difference may be due to the effect of turbulence-like structures formed by strong mass density gradients in real phenomenon.…”
Section: Introductionmentioning
confidence: 99%